Viability of vaginal probiotic lactobacilli during refrigerated and frozen storage - Juárez Tomás, María Silvina (2004)
The viability of six different strains of probiotic vaginal Lactobacillus was examined in two different cryoprotective media, during refrigerated versus frozen storage, and using two traditional types of stock cultures for starting the biomass production. Freezing at -20°C and -70°C had much less adverse effect on viability than did storage at 7°C, and the reduction in viability was greater at -20°C than at -70°C. The strains showed variation in the extent of the viability losses during both types of storage. Milk-yeast extract (MYE) was shown to be the more suitable protective medium to maintain viability of the strains during the storage. The vaginal Lactobacillus strains are most stable in MYE at -70°C with only a small decrease of the viability observed under these conditions. The viable cell counts of Lactobacillus paracasei CRL 1251 and CRL 1289, L. crispatus CRL 1266 and L. salivarius CRL 1328 remained around 1×108CFU/mL after 24 months of storage at -70°C, or up to 18 months for L. acidophilus CRL 1259.